Analisis Proses FSW dan PWHT Material Aluminium Terhadap Kekuatan Tarik, Kekerasan dan Mikrostruktur - Wahyu Ari Putranto; Khaeroman Khaeroman; Heri Kiswanto; Ngatmin Ngatmin; Prijo Harsono; Purwanto Purwanto (Infotekmesin, 2026)
Friction Stir Welding (FSW) is a welding method that does not use filler materials. FSW has been widely used in the maritime industry. The purpose of this study is to analyze the effect of FSW joints before and after Post Weld Heat Treatment (PWHT) on 5052 and 6061 aluminum alloy materials. The FSW parameters include a spindle speed of 1500 rpm (clockwise), a travel speed of 30 mm/min, a tool depth of 0.2 mm, and a tool tilt angle of 1°. The PWHT parameters involve heating the FSW material to 550°C, with holding times of 45 and 90 minutes, followed by water quenching. The subsequent process is artificial aging up to a temperature of 200°C for 6 hours. The materials were then subjected to tensile testing, hardness testing, and micrographic examination. The results showed that the highest values were achieved using FSW parameters with 90 minutes of PWHT, yielding the maximum tensile strength and hardness values of 264 MPa (27.5%) and 89.6 HV (37.4%). Furthermore, the smallest and most uniform grain size was quantitatively observed at 4.9 µm in both the weld zone and the base metal.